Metodologias paramétricas e não paramétricas na inferência da adaptabilidade e estabilidade de linhagens de soja - Silva, Kadson Emmanuel Frutuoso (2017)
Soybeans are a very important crop in the current agricultural setting. The goal of many plant breeding programs is the recommendation of genotypes with satisfactory performance in productivity and stability in different ambient conditions. There are more than a dozen methods adaptability and stability of genotypes that can be employed in an attempt to provide more detailed information on the behavior of each front genotype to environmental variations. Based on this, the objective was to analyze the adaptability and stability of soybean lines by parametric and non-parametric methods. The productivity data were used (kg ha-1) of 24 soybean lines (lines in the final phase) evaluated in 17 environments in the states of Paraná and São Paulo. The experiments were conducted in a randomized block design with three replications in the agricultural year 2012/13. The single largest productivity was presented lineage 5691 (5799 kg ha-1) and the lowest by line 7422 (505 kg ha-1). The inbred lines 6903, 7650 and 7651 showed higher productivity overall average for most environments. It was found that there was agreement in results between the methodologies Eberhart and Russell (1966), Annicchiarico (1992), Cruz et al., (1989), Lin and Binns (1988) and the method of visual examination, sorting 6309 genotype wide adaptability and high stability. The centroid method ranked except the inbred lines 5705 and 6903 with average general adaptability. However, the methods of Huenh (1990) and Fox et al. (1990) classified it as best genotype sinbred lines 5745, 7650 and 7651 is introducing high stability and moderate productivity.